Association of Teaching Status and Mortality After Cancer Surgery. Issue 3 (23rd September 2021) - Lam, Miranda B.; Riley, Kristen E.; Mehtsun, Winta; Phelan, Jessica; Orav, E. John; Jha, Ashish K.; Burke, Laura G.
Abstract : Objective: To examine patient outcomes for 9 cancer-specific procedures performed in teaching versus nonteaching hospitals. Background: Few contemporary studies have evaluated patient outcomes in teaching versus nonteaching hospitals across a comprehensive set of cancer-specific procedures. Methods: Use of national Medicare data to compare 30-, 60-, and 90-day mortality rates in teaching and nonteaching hospitals for cancer-specific procedures. Risk-adjusted 30-day, all-cause, postoperative mortality overall and for each specific surgery, as well as overall 60- and 90-day mortality rates, were assessed. Results: The sample consisted of 159, 421 total cancer surgeries at 3151 hospitals. Overall 30-day mortality rates, adjusted for procedure type, state, and invasiveness of procedure were 1.3% lower at major teaching hospitals (95% confidence interval [CI], −1.6% to −1.1%; P < 0.001) relative to nonteaching hospitals. After accounting for patient characteristics, major teaching hospitals continued to demonstrate lower mortality rates compared with nonteaching hospitals (−1.0% difference [95% CI, −1.2% to −0.7%]; P < 0.001). Further adjustment for surgical volume as a mediator reduced the difference to −0.7% (95% CI, −0.9% to −0.4%; P < 0.001). Cancer surgeries for 4 of the 9 disease sites (bladder, lung, colorectal, and ovarian) followed this overall trend. Sixty- and 90-day overall mortality rates, adjusted for procedure type, state, and invasiveness of procedure showed that major teaching hospitals had a 1.7% (95% CI, −2.1% to −1.4%; P < 0.001) and 2.0% (95% CI, −2.4% to −1.6%; P < 0.001) lower mortality relative to nonteaching hospitals. These trends persisted after adjusting for patient characteristics. Conclusions: Among cancer-specific procedures for Medicare beneficiaries, major teaching hospital status was associated with lower 30-, 60-, and 90-day mortality rates overall and across 4 of the 9 cancer types.